KUALITAS AIR MINUM ISI ULANG PADA DEPOT AIR MINUM (DAMIU) DI WILAYAH KERJA PUSKESMAS OEPOI KOTA KUPANG - ALBINA BARE TELAN; AGUSTINA AGUSTINA; OLGA MARIANA DUKABAIN (JURNAL INFO KESEHATAN, 2015)
Water is part of the physical environment that absolutely must exist for the survival of human life, animals, and plants. But other than useful for life, water can also be detrimental in the event of water contamination. Water contamination can occur due to physical contamination, contamination of chemicals in the form of organic and inorganic chemicals and the presence of biological contaminants that have microorganisms such as pathogenic bacteria, which deviate from the specified standard of health requirements. In recent years the business of refill drinking water has been growing rapidly in several cities in Indonesia including Kota Kupang. Needs the drinking water community continues to increase as population growth, not offset by the availability of clean water available. Refill drinking water is one of the answers to meet the needs of drinking water Indonesian people are cheap and practical. This is the reason why people choose refill drinking water for consumption. This study aims to determine the quality of drinking water at refill drinking water depots (DAMIU) working area of public health center Oepoi Kota Kupang. This type of research is descriptive research, with the research design is cross-sectional study. The population and samples in this study are the drinking water depots located in the working area of the Oepoi community health center determined by the community health center of the working area of 25 Depot refill drinking water (DAMIU). The results showed that the physical qualities of water are eligible ie odorless, tasteless and colorless, while the water quality of the chemical ie the level of hardness also meets the requirements of the average below 500 mg/liter, and the results of the quality of bacteriological is not qualified because there are still 10 (40%) DAMIU water contains coliform bacteria and 5 (20%) DAMIU water contains bacteria e.coli. It is advisable To the owners of DAMIU to pay more attention to hygiene and sanitation during the production process because it is very influential on the quality of drinking water refills produced for example routinely perform cleaning at least once a month and supervision from parties related to being tightened.